FUNGSI DAN MAKNA TRADISI CUKUR RAMBUT DALAM MASYARAKAT MELAYU DESA RAMBAH SAMO BARAT - Lita Syahrini; Nuratika Nuratika (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2026)
The tradition of hair-cutting (cukur rambut) is a cultural heritage that is still preserved by the Malay community in Rambah Samo Barat Village, Rokan Hulu Regency. This study aims to analyze the functions and meanings of the hair-cutting tradition so that the community can understand its essence and distinguish it from the aqiqah religious practice. The method used in this research is qualitative, with the researcher serving as the primary instrument. Data were obtained through observation and in-depth interviews with local traditional leaders, which were then analyzed using Soerjono Soekanto's sociological theory. The results show that the functions of the hair-cutting tradition include aspects of historical heritage, reinforcement of family identity through the father's role, and as a means of entertainment and social integration. Meanwhile, the meaning of this tradition is reflected in religious and simplicity values, the fulfillment of children's rights to care, and the process of early socialization of moral and traditional values. Through this understanding, it is expected that misunderstandings between the hair-cutting tradition and the aqiqah obligation can be minimized.